RF17 What makes adolescents binge drink so often? research evidence from a population school survey in chile. (September 2018) - Roman, MF; Cable, N
Abstract : Background: Binge drinking is known to cause alcohol-related harm among young people. Although the link between adolescent binge drinking and adolescents' own, parental or peer factors were established, little is known about the factors that associate with the frequency of binge drinking in the school contexts. The aim of this study is to examine the contextual associations between parental, peer and school factors and the frequency of binge drinking among Chilean school children aged 13 to 18. We hypothesised that severe school level deprivation would be associated with an increased number of binge drinking events as well as lower levels of parental supervision, and parental and peer drinking. Data: Information on frequency of binge drinking in the past month, parental supervision, paternal and maternal drinking and peer drinking was extracted from the Tenth Chilean School Population National Substance Use Survey conducted in 2013. Frequency of binge drinking was analysed among those reporting alcohol use. The individual-level information was linked to school-level information (percentage of free school meal children) obtained from the Ministry of Education Methods: Hierarchical data, individuals (n=41, 146) nested within schools (n=1, 687), were analysed using multilevel zero-inflated Poisson regression. Coefficients from the Poisson part were exponentiated to obtain Incidence Rate Ratios (IRR). Estimates were adjusted for parental education, child's age and school type and boys and girls were analysed separately. Results: Results from the Poisson part in the final model showed significant associations between lower levels of parental supervision and increased binge drinking frequencies in boys and girls. For girls, maternal drinking during weekends increased their binge drinking episodes by 10% (IRR=1.11 95% CI 1.03; 1.20), while mother's daily drinking habits increased them by 24% (IRR=1.24 95% CI 1.18; 1.38). Maternal daily drinking also showed increases in boy's binging episodes by 21% (IRR=1.21 95% CI 1.11; 1.31). Having at least half of friends that consumed alcohol increased the average number of binge drinking episodes by 21% (IRR=1.21 95% CI 1.13; 1.28) for boys, but by 60% (IRR=1.58 95% CI 1.45; 1.71) for girls. School deprivation was positively associated with the number of events of binge drinking for girls only (IRR=1.0034 95% CI 1.002; 1.005). Norms, especially mother's supporting alcohol use and peer influences were major contributor for frequent binge drinking among Chilean adolescents. Girls are likely to be more vulnerable to frequent binge drinking, influenced by their peer groups and school environment.